2020
DOI: 10.1002/jmri.27369
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model Combining Clinical and MR Data for Diagnosis of Lymph Node Metastasis in Patients With Rectal Cancer

Abstract: Background Determining the status of lymph node (LN) metastasis in rectal cancer patients preoperatively is crucial for the treatment option. However, the diagnostic accuracy of current imaging methods is low. Purpose To develop and test a model for predicting metastatic LNs of rectal cancer patients based on clinical data and MR images to improve the diagnosis of metastatic LNs. Study type Retrospective. Subjects In all, 341 patients with histologically confirmed rectal cancer were divided into one training s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous studies have reported the diagnostic value of radiomics models in predicting LN metastasis in rectal cancer ( 17 19 , 28 34 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the diagnostic value of radiomics models in predicting LN metastasis in rectal cancer ( 17 19 , 28 34 ). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics‐based approaches enable the assessment of tumor characteristics, such as size, shape, texture, and heterogeneity, thus aiding the prediction of treatment outcomes and selection of optimal treatment strategies [22]. Combined with clinical data and molecular markers, radiomic features contribute to the development of precision medicine for CRC [23]. Radiomics identifies imaging‐based biomarkers of treatment response and prognosis.…”
Section: Radiomics In Colorectal Cancermentioning
confidence: 99%
“…The characteristics of the studies are presented in Table 1. The reference standards were divided into the following five categories according to different morphological criteria: (A) a short-axis diameter of 5 mm (22-34), (B) morphological standard, including an irregular border and mixed-signal intensity within the lymph node (35)(36)(37)(38)(39)(40), (C) a short-axis diameter of 5 mm with the morphological standard (11,(41)(42)(43)(44)(45)(46)(47)(48), (D) a short-axis diameter of 8 mm with the morphological standard (49)(50)(51)(52), and (E) a short-axis diameter of 10 mm with the morphological standard (11,45,53,54). In all of the included articles, 36 indirectly evaluated the lymph node stage of patients through histopathology and 5 (9,41,42,55,56) identified the node-by-node correspondence between lymph node MRI scans and histopathologic results.…”
Section: Description Of Included Studiesmentioning
confidence: 99%